Assessment of village health volunteers role perceptions about prevention and control of dengue haemorrhagic fever in Thungsong district, Nakhon Si Thammarat province, Thailand - Nikorn Kuntong (Chulalongkorn University, 2014)
Thesis (M.P.H.) -- Chulalongkorn University, 2006